ANALISIS RASIO LIKUIDITAS, PROFITABILITAS, AKTIVITAS, SOLVABILITAS DAN INVESTMENT OPPORTUNITY SET DALAM TAHAPAN SIKLUS KEHIDUPAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK JAKARTA (BEJ) TAHUN 2001 – 2005. - HAMZAH, ARDI (Jurnal Ilmiah Akuntansi dan Bisnis, 2007)
The objective of this research is to analysis of liquidity, profitability, activity andsolvency ratios on investment opportunity set (IOS) in the stages of life cycle ofmanufacturing firms that are listed on the Jakarta Stock Exchange. The sample of the studyare manufacture firms listed on the Jakarta Stock Exchange that distributed dividendsuccessively in 2001 – 2005. Sample size consists of total is 135 firms.This study indicates that on the start-up stage, activity and solvency ratios have effecton IOS. On the initial expansion stage, activity ratio has effect on IOS and on the finalexpansion no ratio has effect on IOS. For mature and decline stages, also no ratio has effecton IOS. Therefore, financial ratios can be used manufacture firm analysis tools at start-upand initial expansion stages, but not at final expansion, mature and decline stages.
Keywords: liquidity, profitability, activity, solvency, investment opportunity set, manufacturing firms